2014
DOI: 10.1002/jcla.21666
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Screening and Confirmatory Serological Assays in Blood Donors in a Region of South Italy

Abstract: Supplemental testing on samples with high signal by screening assays seems to add little information. GZ settings and confirmatory testing for positive screening results should be designed taking in account several factors, including difference in the natural history among blood-borne infections, the characteristics of first- and second-level tests, and, when available, the results of nucleic acid amplification testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…The overall specificity results reported here were similar for the Elecsys syphilis assay and all other assays tested (Table 2) and compare favorably with those reported in the literature (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as shown in Fig. 1A.…”
Section: Discussionsupporting
confidence: 89%
“…The overall specificity results reported here were similar for the Elecsys syphilis assay and all other assays tested (Table 2) and compare favorably with those reported in the literature (26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), as shown in Fig. 1A.…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of confirmed active infections among positive screening test results varies widely across studies and test types. The proportion of RNA-positive, active HCV infection cases ranged from 0% to 89.7% among positive antibody-based assays [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][45][46][47][48][51][52][53][54] and from 0% to 100% among antigen-based assays. 39,44,49,50 Only three studies conducted confirmatory polymerase chain reaction on samples that tested negative for HCV antibody or antigen.…”
Section: Box 1: Grading Of Recommendationsmentioning
confidence: 99%
“…The proportion of negative anti-HCV assays that were confirmed with polymerase chain reaction to be RNA negative ranged from 73.7% to 99.7% for two antibody assays 29,39 and 89.7% in one antigen assay. 32 The wide variation in results may be as a result of actual differences in test performance, varying study sample sizes or underlying variation in population characteristics, including population prevalence.…”
Section: Box 1: Grading Of Recommendationsmentioning
confidence: 99%
“…Although automated CLIAs are gradually replacing EIAs, data from published studies have compared the results obtained with algorithms that use the two techniques (9, 10, 12, 1517). It has been reported that the detection of infection markers requires all screening assays to have high levels of sensitivity and specificity (911, 18). The present study demonstrated for the first time that the use of an algorithm based on automated CLIAs before GI endoscopy increased the sensitivity of detection of HIV, HCV, and HBV, increased the specificity of detection of HIV, and maintained the specificity of detection of HCV, HBV, and T.…”
Section: Discussionmentioning
confidence: 99%
“…All proposed algorithms should have a high level of sensitivity and specificity for testing for blood-transmitted infections to ensure safety during surgery (911). The selection of appropriate algorithms and assays is a critical part of the screening program, and enzyme immunoassays (EIAs) and chemiluminescent immunoassays (CLIAs) are currently the assays that are the most frequently employed in these serological screening algorithms (913).…”
Section: Introductionmentioning
confidence: 99%